Within-host evolution of Burkholderia pseudomallei in four cases of acute melioidosis. - Erin P Price (PLoS Pathogens, 2010)
Little is currently known about bacterial pathogen evolution and adaptation within the host during acute infection. Previous studies of Burkholderia pseudomallei, the etiologic agent of melioidosis, have shown that this opportunistic pathogen mutates rapidly both in vitro and in vivo at tandemly repeated loci, making this organism a relevant model for studying short-term evolution. In the current study, B. pseudomallei isolates cultured from multiple body sites from four Thai patients with disseminated melioidosis were subjected to fine-scale genotyping using multilocus variable-number tandem repeat analysis (MLVA). In order to understand and model the in vivo variable-number tandem repeat (VNTR) mutational process, we characterized the patterns and rates of mutations in vitro through parallel serial passage experiments of B. pseudomallei. Despite the short period of infection, substantial divergence from the putative founder genotype was observed in all four melioidosis cases. This study presents a paradigm for examining bacterial evolution over the short timescale of an acute infection. Further studies are required to determine whether the mutational process leads to phenotypic alterations that impact upon bacterial fitness in vivo. Our findings have important implications for future sampling strategies, since colonies in a single clinical sample may be genetically heterogeneous, and organisms in a culture taken late in the infective process may have undergone considerable genetic change compared with the founder inoculum.